Dual-band multiple-element MIMO antenna system for next-generation smartphones - Kiani, Saad Hassan; Marey, Mohamed; Savcı, Hüseyin Şerif; Mostafa, Hala; Rafique, Umair; Khan, Muhammad Amir (MDPI (Multidisipliner Digital Publishing Institute), 2022)
This work presents a cost-effective multiple-element multiple-input multiple-output (MIMO) antenna system for next-generation smartphones. The proposed antenna system is developed on a 0.8 mm thin FR-4 substrate with a relative permittivity of 4.4, which consists of one main board and two sideboards. The dimensions of the main board and the two side boards are 150 × 75 mm2 and 150 × 6 mm2, respectively. The radiating elements are printed on the sideboards to provide space for other radio frequency (RF) components to be embedded on the main board. The proposed antenna resonates at two distinct allotted 5G bands, i.e., 3.5 GHz and 5.4 GHz, with impedance bandwidths of 200 MHz and 700 MHz, respectively. The isolation between the antenna elements is noted to be >18 dB and >12 dB for the 3.5 GHz and 5.4 GHz frequency bands. In addition, the proposed MIMO antenna provides pattern and spatial diversity characteristics in both bands with good gain and efficiency. Furthermore, the MIMO parameters such as envelope correlation coefficient (ECC), mean effective gain (MEG), and channel capacity (CC) are calculated, and it is observed that the MIMO antenna offers good diversity performance for the bands of interest. A prototype is fabricated and measured to verify the numerical data. The simulated results were discovered to be in excellent agreement with the measured results. It is also observed that the proposed MIMO antenna system holds promising features, and can be utilized for future generations of smartphones.
Keywords: 5G; Dual-Band; MIMO; Pattern Diversity